THE EVALUATION OF MYSPADA LMS IN SUPPORTING AUTONOMOUS LEARNING OF ENGLISH EDUCATION DEPARTMENT STUDENTS - Hanif Afifurrohman; Hepy Adityarini (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
This study evaluated MySpada Learning Management System's effectiveness in supporting autonomous learning among English Education students at Universitas Muhammadiyah Surakarta. Using a mixed-methods approach, data were collected from 39 students through document analysis, semi-structured interviews (n=4), and questionnaires (n=35). Results showed that 71.4% of students recognized MySpada's features as supportive, yet only 37.1% agreed it enhanced learning discipline and 48.6% felt motivated. Students primarily accessed learning materials (53.6%) but rarely used discussion forums (10.7%). Technical challenges including server instability, slow performance, and mobile accessibility issues significantly hindered effectiveness. The gap between feature recognition and behavioral impact suggests MySpada functions as a content repository rather than an active facilitator of self-regulated learning. To optimize MySpada’s role, the university should prioritize strengthening server stability and mobile optimization to ensure reliable access during high-traffic periods. The study further recommends integrating progress-tracking dashboards and goal-setting tools to transform the platform from a passive content repository into an active facilitator of self-regulation. Finally, establishing consistent faculty usage through pedagogical training and institutional policy is essential to sustain student engagement and maximize the platform’s effectiveness in fostering autonomy